SISTEM INFORMASI PENJUALAN SPECIALIZED IN PLASTIC CONTAINERS AND PACKAGINGS BERBASIS WEB : (Studi Kasus PT. ILUFAK PLASKAGING Semarang) - Minarida Nova Yuspita; Danang Danang (Pusat Riset dan Inovasi Nasional, 2024)
Recent developments in all fields have provided many advantages in various aspects of human life. These developments have brought people to always move dynamically because they are required to always follow it. The ability to access information will be very helpful in the development process of human life itself. In line with the advancement of information technology today, all business fields are required to be able to keep up with very rapid and fast developments. In the preparation of the thesis carried out at PT. ILUFAK Plaskaging Semarang authors can conclude that there are many benefits of making a web-based Sales information system. The benefit is that it can help smooth, precise and work efficiency in the system of selling goods. In making this Web-based sales information system, the author uses the application program Macromedia Dreamwever MX 2004, Adobe Photoshop CS2, to support the creation of online sales programs.